Efficient P2P data dissemination in integrated optical and wireless networks with Taguchi method - M. A. Wong; Jamil Abedalrahim Jamil Alsayaydeh; Sevia Mahdaliza Idrus; Nadiatulhuda Zulkifli; M. Elshaikh (Universitas Ahmad Dahlan, 2019)
The Quality of Service (QoS) resource consumption is always the tricky problem and also the on-going issue in the access network of mobile wireless part because of its dynamic nature of network wireless transmissions. It is very critical for the infrastructure-less wireless mobile ad hoc network that is distributed while interconnects in a peer-to-peer manner. Toward resolve the problem, Taguchi method optimization of mobile ad hoc routing (AODVUU) is applied in integrated optical and wireless networks called the adLMMHOWAN. Practically, this technique was carry out using OMNeT++ software by building a simulation based optimization through design of experiment. Its QoS network performance is examined based on packet delivery ratio (PDR) metric and packet loss probabilities (PLP) metric that consider the scenario of variation number of nodes. During the performing stage with random mobile connectivity based on improvement in optimized front-end wireless domain of AODVUU routing, the result is performing better when compared with previous study called the oRia scheme with the improvement of 14.1% PDR and 43.3% PLP in this convergence of heterogeneous optical wireless network.